(untitled) (Open International Journal of Informatics, 2021)
Recently, there has been an increased interest in research on the usage of technology in handwriting especially among children across the world but rarely in Malaysia. Therefore, there is a need to research the patterns and research gaps related to the usage of technology in handwriting, especially in preschool children. In this paper, a meta-analysis study was performed on articles related to technology, handwriting and children from the year 2015 until 2020. The main findings from the analysis show that most of the previous studies used stylus pen on tablet compared to other digital tools to assess handwriting performance, and a quantitative research approach using experimental design was used to test the performance. These findings can be used as a reference for researchers in education, especially in the early childhood field to carry out research related to this scope of interests. This paper also provides suggestions for further relevant research in a similar context.